Childhood maltreatment and vulnerability to substance use disorders: The mediating role of psychological security - Behzad Shalchi; Maryam Nosrati Beighzadeh; Ali Reza Shafiee-Kandjani; Hassan Shahrokhi; Behnaz Hoseinzadeh Khanmiri (Tabriz University of Medical Sciences, 2024)
Background: Understanding the factors associated with the propensity for drug dependence might be helpful in providing the best strategies for substance use prevention among youth. The present study was conducted to examine the association between childhood maltreatment (CM) and susceptibility to substance use disorders (SUDs), taking into account the mediating role of psychological safety. Methods: In this cross-sectional study, multistage cluster sampling was employed to recruit 400 male students from the three universities of Tabriz in 2019. Research instruments included the valid and reliable scales of substance abuse, childhood trauma, and mental safety. Data were analyzed using Pearson correlation, and structural equation modeling. Results: The results showed positive significant relationships between vulnerability to SUDs, CM, and low levels of psychological safety. The evaluation of our hypothetical research model using fit indices showed that the model fits well the measurement model (CFI=0.97, GFI=0.95, RMSEA=0.058). Conclusion: Our proposed theoretical model suggested psychological security as a mediator between CM and SUDs. CM explained addiction in college students through reducing psychological security. Investigating these interactive processes seems to be detrimental, considering that they may enhance our understanding of the ways to reduce the risk.